Studies in Islamic Legal Theory - Weiss, Bernard (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
This volume is unique as a collection of studies devoted entirely to topics and issues in the field of Islamic legal theory and authored by fourteen scholars known for their work in this field. The studies deal with such topics as early notions of charismatic authority, hermeneutic techniques in Shāfiʿī's Risālah , uses of the term sunnah in the ninth century A.H., evidence for the emergence of usūl al-fiqh as a genre of legal literature in the ninth century, the function of usūl al-fiqh in relation to legal practice, theological ramifications of issues in usūl al-fiqh , Shīʿī attitudes to qiyās , the structure of juristic authority within the madhhab , usūl al-fiqh as an instrument of reform, the place of qawāʿid within Islamic legal theory. These studies are followed by a discussion among the authors.